Integrasi Tradisi Adat dan Strategi Kepolisian Modern dalam Penyelesaian Konflik Sosial - Kamil, Muhamad Adin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Social conflict is a complex phenomenon that often arises in communities amidst cultural, economic, and political differences. Effective conflict resolution requires an adaptive approach, combining local wisdom and modern practices. This article discusses the integration of customary traditions and modern police strategies in handling social conflict. Customary traditions, with their long-standing mechanisms of mediation and deliberation, play a role in maintaining harmony and building trust among residents. Meanwhile, modern police strategies offer a law-based approach, security enforcement, and systematic risk management. The integration of these two approaches provides a more comprehensive solution, minimizes conflict escalation, and increases community participation in the resolution process. The study's findings indicate that the synergy between customary values and modern police methods is not only effective in reducing conflict but also strengthens social cohesion and the legitimacy of officers within the community.